An Analysis of the Use of Music as Stroke Therapy Among the Congregation of GBI Victory Poris Indah - Lidya Elisabeth (Riviera Publishing, 2026)
This research aims to analyze the use of music as a therapeutic intervention in the stroke recovery process of a pastor from GBI Victory Poris Indah, who served as the main subject (HK). Stroke is a neurological disorder that not only affects physical function but also causes psychological problems such as anxiety, stress, and reduced quality of life. This research employs a qualitative approach with a narrative descriptive design. Data were collected through in-depth interviews, observations, and documentation involving three informants, including the main subject and two companions during the recovery process. The findings reveal that HK unconsciously applied music therapy through three main activities: listening to spiritual and instrumental music, singing combined with breathing exercises, and writing as well as composing song lyrics. These activities were performed consistently every day during the post-stroke recovery period. The results indicate positive changes in emotional, physiological, and cognitive conditions, including reduced anxiety levels, improved emotional stability, enhanced speech function, and gradual recovery of motor abilities. Theoretically, the findings support the concept of brain neuroplasticity, which suggests that repeated stimulation such as music can promote the formation of new neural connections in damaged brain areas. Moreover, music acts as a positive distraction that reduces sympathetic nervous system activity. Therefore, music can be considered a potential non-pharmacological intervention that supports independent and holistic stroke rehabilitation.